1998
DOI: 10.1159/000015149
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and mapping of the human SOX14 gene

Abstract: SOX genes comprise a family of genes that are related to the mammalian sex determining gene SRY in the region that encodes the HMG-box domain responsible for the sequence-specific DNA-binding activity. SOX genes encode putative transcriptional regulators implicated in the decision of cell fates during development and the control of diverse developmental processes. We have cloned and characterised SOX14, a novel member of the human SOX gene family. Based on the HMG-box sequence, human SOX14 is a member of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
25
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 40 publications
6
25
1
Order By: Relevance
“…Both the mouse and chick Sox14 coding regions are encoded by a single exon (Hargrave et al 2000b) and comparison of the human SOX14 coding region with mouse and chick Sox14 cDNA sequence indicates that the human SOX14 coding region is also intronless. This observation is in agreement with the data of Arsic et al (1998) who utilised a reverse transcription/PCR (RT-PCR)-based approach to determine the structure of SOX14. The human SOX14 putative protein, like that in mouse and chick, is 240 amino acid residues in length and contains an N-terminal HMG box and a C-terminus con-434 Fig.…”
Section: Cloning Of Human Sox14supporting
confidence: 91%
See 3 more Smart Citations
“…Both the mouse and chick Sox14 coding regions are encoded by a single exon (Hargrave et al 2000b) and comparison of the human SOX14 coding region with mouse and chick Sox14 cDNA sequence indicates that the human SOX14 coding region is also intronless. This observation is in agreement with the data of Arsic et al (1998) who utilised a reverse transcription/PCR (RT-PCR)-based approach to determine the structure of SOX14. The human SOX14 putative protein, like that in mouse and chick, is 240 amino acid residues in length and contains an N-terminal HMG box and a C-terminus con-434 Fig.…”
Section: Cloning Of Human Sox14supporting
confidence: 91%
“…3). This position is consistent with the position inferred by FISH and other independent investigations of the chromosomal position of SOX14 (Arsic et al 1998;Malas et al 1999). Recently, a 155-kb human genomic sequence from a human male bacterial artificial chromosome (BAC) clone (clone 2_A_4, accession no.…”
Section: Chromosomal Localisation Of Human Sox14supporting
confidence: 88%
See 2 more Smart Citations
“…In our study we found that the seven E. breuchleyi Sox genes did not cluster together but were distributed between the B and C Sox groups. It is known that Sox1, Sox2 and Sox3 are members of the family of HMG DNA-binding domain containing transcription factors related to the testis-determination Sry gene and, along with the recently discovered Sox14 and Sox21 genes, comprise the group B subfamily of Sox genes (Collignon et al, 1996), while the members of group C (Sox4, Sox11, Sox12, Sox22 and Sox24) encode highly conserved N-and C-terminal amino acid sequences (Collignon et al, 1996;Pevny and Lovell-Badge, 1997;Arsic et al, 1998;Rex et al, 1997;Kamachi et al, 1995;Hargrave et al, 2000;Uchikawa et al, 1999). It should be remembered, however, that the PCR primer set used by us may have had a bias leading to preferential amplification of group B and C E. breuchleyi Sox genes.…”
mentioning
confidence: 99%